1984
DOI: 10.1007/bf02294170
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sampling error on convergence, improper solutions, and goodness-of-fit indices for maximum likelihood confirmatory factor analysis

Abstract: Confirmatory factory analysis, LISREL, Monte Carlo, Maximum likelihood,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
757
3
116

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,450 publications
(912 citation statements)
references
References 16 publications
36
757
3
116
Order By: Relevance
“…Therefore, the proposed models were re-tested using separated data for China and Korea (N=192 for China and N=122 for Korea). It was assumed that the sample sizes for China and Korea were adequate, because previous studies had reported that a sample size of 100 is usually sufficient for convergence (Anderson and Gerbing, 1984;Iacobucci, 2010). Fit indices for both path models for the two countries showed acceptable levels (RMSEA = 0.06, GFI =0.90, and 2 /df=1.14 for China and RMSEA = 0.03, GFI =0.91, and 2 /df=1.89 for Korea).…”
Section: Cross-cultural Comparisonmentioning
confidence: 99%
“…Therefore, the proposed models were re-tested using separated data for China and Korea (N=192 for China and N=122 for Korea). It was assumed that the sample sizes for China and Korea were adequate, because previous studies had reported that a sample size of 100 is usually sufficient for convergence (Anderson and Gerbing, 1984;Iacobucci, 2010). Fit indices for both path models for the two countries showed acceptable levels (RMSEA = 0.06, GFI =0.90, and 2 /df=1.14 for China and RMSEA = 0.03, GFI =0.91, and 2 /df=1.89 for Korea).…”
Section: Cross-cultural Comparisonmentioning
confidence: 99%
“…SEM is also important for validity testing and construct validation, because it focuses on the distinction between the measurement model and the structural model, but also allows more rigorous tests of construct reliability, convergent validity and discriminant validity (Anderson and Gerbing, 1984;Malhotra et al, 1999;Jarvis et al, 2003;MacKenzie et al, 2005).…”
Section: Semmentioning
confidence: 99%
“…We note that we reduced the number of parameters to be estimated by calculating a path analytic model and not a full structural equation model with a measurement and a structural model. We further used maximum-likelihood estimation which should also contribute to the robustness of our findings; Monte Carlo studies showed that bias in parameter estimates is of no practical importance for sample sizes as low as 50 in the case of maximum-likelihood estimations (Anderson & Gerbing, 1984;Gerbing & Anderson, 1985). Statistical inferences based on tests of significance remain valid because standard errors of the path coefficients are adjusted according to the sample size.…”
Section: Limitationsmentioning
confidence: 99%